2003
DOI: 10.1002/chin.200304129
|View full text |Cite
|
Sign up to set email alerts
|

Structure—Activity Relationships of Some 3‐Substituted‐4‐hydroxycoumarins as HIV‐1 Protease Inhibitors.

Abstract: are synthesized and their HIV-1 antiprotease activity is determined. -(KIRKIACHARIAN*, S.; DUONG THANH THUY; SICSIC, S.; BAKHCHINIAN, R.; KURKJIAN, R.; TONNAIRE, T.; Farmaco 57 (2002) 9, 703-708; Lab. Chim. Therap., Fac. Pharm., BIOCIS, F-92296 Chatenay-Malabry, Fr.; Eng.) -R. Langenstrassen 04-129

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…According to Semple et al (1998Semple et al ( ,1999, Pterocaulon sphacelatum has antiviral activity suggesting that other species from Pterocaulon genus may also have antiviral activity. Coumarins have been related to HIV-1 protease inhibitory activity (Kirkiacharian et al, 2002). Our results In vitro cytotoxic, antioxidant and antiviral effects of Pterocaulon alopecuroides and Bidens segetum extracts suggest that 7-(2',3'-dihidroxy-3'-methylbutyloxy)-6-methoxycoumarin can be responsible to the Herpes simplex virus inhibitory activity.…”
Section: Resultsmentioning
confidence: 54%
“…According to Semple et al (1998Semple et al ( ,1999, Pterocaulon sphacelatum has antiviral activity suggesting that other species from Pterocaulon genus may also have antiviral activity. Coumarins have been related to HIV-1 protease inhibitory activity (Kirkiacharian et al, 2002). Our results In vitro cytotoxic, antioxidant and antiviral effects of Pterocaulon alopecuroides and Bidens segetum extracts suggest that 7-(2',3'-dihidroxy-3'-methylbutyloxy)-6-methoxycoumarin can be responsible to the Herpes simplex virus inhibitory activity.…”
Section: Resultsmentioning
confidence: 54%
“…Because of their sweet scent, readily recognized as the scent of newly-mown hay, coumarins have been used in perfumes since 1882. In addition to their use in perfumes, coumarins also constitute an important class of natural and synthetic products [4,5]. For instance, warfarin, a synthetic derivative of coumarin and also known under the brand names "Coumadin," "Jantoven," "Marevan," "Lawarin," and "Waran" is commonly used as an anticoagulant.…”
Section: Coumarin Dyesmentioning
confidence: 99%
“…The results demonstrated that any hydroxyl group nearer to the 4hydroxyl group interfere with the hydrogen bond between this group and Asp25/Asp25 0 of HIV-1 protease however, distant 7hydroxy derivatives were most active anti-HIV agents. Replacement of 3-phenyl with benzyl group indicates that flexibility did not lead to any significant change in activity [39]. Similarly, another scientist Stanchev et al also reported some 4-HC derivatives as HIV-1 protease inhibitors.…”
Section: Introductionmentioning
confidence: 98%